Volume 4: Heat Transfer, Parts a and B 2012
DOI: 10.1115/gt2012-69566
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Characteristics of an Angled Array Impinging Jet on a Concave Duct

Abstract: This study investigated the heat transfer characteristics of an array jet cooling system on a concave surface. Two types of injection holes were used: one for impinging jets normal to the impingement surface, and the other for angled impinging jets. For the normal jets, the jet Reynolds number (Re) based on the hole diameter varied from 3,000 to 10,000, and the height-to-diameter ratio (H/d) was fixed at 1.0. There were 15 injection holes positioned in a staggered 3×5 array. For the angled jets, Re was set to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Different jet hole shapes [1][2][3][4], the arrangement of the jet holes [5][6][7][8], and the jet plate-target plate distances [3] were taken into account, and geometric optimization studies have been carried out in the literature. Additionally, Jung et al [1,9] compared the heat transfer characteristics of a standard and inclined jet array. Their findings showed that the inclined jet design exhibited higher heat transfer performance than the standard jet configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Different jet hole shapes [1][2][3][4], the arrangement of the jet holes [5][6][7][8], and the jet plate-target plate distances [3] were taken into account, and geometric optimization studies have been carried out in the literature. Additionally, Jung et al [1,9] compared the heat transfer characteristics of a standard and inclined jet array. Their findings showed that the inclined jet design exhibited higher heat transfer performance than the standard jet configuration.…”
Section: Introductionmentioning
confidence: 99%